Herpesvirus Late Gene Expression: A Viral-Specific Pre-initiation Complex Is Key - Gruffat, Henri; Marchione, Roberta; Manet, Evelyne (Frontiers in Microbiology, 2016)
During their productive cycle, herpesviruses exhibit a strictly regulated temporal cascade of gene expression that can be divided into three general stages: immediate-early (IE), early (E) and late (L). This expression program is the result of a complex interplay between viral and cellular factors at both the transcriptional and post-transcriptional levels, as well as structural differences within the promoter architecture for each of the three gene classes. Since the cellular enzyme RNA polymerase II (RNAP-II) is responsible for the transcription of herpesvirus genes, most viral promoters contain DNA motifs that are common with those of cellular genes, although promoter complexity decreases from immediate-early to late genes. Immediate-early and early promoters contain numerous cellular and viral cis-regulating sequences upstream of a TATA box, whereas late promoters differ significantly in that they lack cis-acting sequences upstream of the Transcription Start Site (TSS). Moreover, in the case of the β- and γ-herpesviruses, a TATT box motif is frequently found in the position where the consensus TATA box of eukaryotic promoters usually localizes. The mechanisms of transcriptional regulation of the late viral gene promoters appear to be different between α-herpesviruses and the two other herpesvirus subfamilies ( and ). In this review, we will compare the mechanisms of late gene transcriptional regulation between HSV-1, for which the viral IE transcription factors - especially ICP4 - play an essential role, and the two other subfamilies of herpesviruses, with a particular emphasis on EBV, which has recently been found to code for its own specific TATT-binding protein.